Evaluation of the Nazaré canyon's influence in the maritime agitation of the region through the SWAN model application - Forone, Eduardo (2015)
This dissertation has the main purpose of analyzing the Nazaré canyon influence in the region´s maritime agitation trough the application of the SWAN (Simulating WAves Nearshore) mathematical model. To understand the impact of the Nazaré canyon, a synthetic scenario was defined, apart from the real scenario, where the Nazaré canyon was completely fulfilled with sediments and the numerical bathymetry was modified, using a tool from the MOHID modeling system, in a way that the seafloor was like a normal beach brake. The SWAN model was applied for several different forcing conditions and it were analyzed the height, period, direction, length and orbital speed´s results. The results of the simulations performed by SWAN along the Nazaré coast, in different scenarios, confirm the importance of the Nazaré canyon in the wave circulation in this region. In general, all parameters had specific changes, but the changes in wave direction, wave height and orbital velocity, are the ones that showed differences that would cause a highest impact on the wave circulation in the region.